MANAJEMEN PEMBELAJARAN ALQURAN SISWA KELAS I MIS AL-AFKARI PADA MASA COVID 19 - Nasution, Zulkipli (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2020)
The learning of the Koran carried out at MIS Al-Afkari is one of the main lessons at the elementary level. Learning will be maximized when supported by good learning management. The management of learning that is carried out greatly determines the success of learning objectives that have been set. The urgency of learning management will be even more important when faced with obstacles that are passed in the learning process with limitations owned by students in the learning process, either due to the level of students still in grade 1 or learning limitations due to the covid 19. Conditions with the condition of learning limitations caused by covid 19 and age who are still young, of course the learning process of the Koran class 1 students must be managed well, so that the role of learning management functions well even with the obstacles encountered in the learning process of the Koran. The formulation of the problem in this study is how the management of learning the Koran of students of class 1 MIS Al-Afkari Batang Quiz during covid 19. The purpose of this study is to find out how the learning management elements of class 1 MIS Al-Afkari students, including: planning, organizing, implementing and implementing evaluation in learning the Koran students grade 1 MIS Al-Afkari Batang Quiz on covid 19.